Design, synthesis, and antitumor efficacy of novel 5-deazaflavin derivatives backed by kinase screening, docking, and ADME studies - Walaa A. Bedewy; Mosaad S. Mohamed; Ahmed M. Abdelhameed; Mohamed A. Elsawy; Mohammed Al-Muhur; Noriyuki Ashida; Ashraf N Abdalla; Tamer A. Elwaie; Tomohisa Nagamatsu; Hamed I. Ali (Taylor & Francis Group, 2023)
Novel 5-deazaflavins were designed as potential anticancer candidates. Compounds 4j, 4k, 5b, 5i, and 9f demonstrated high cytotoxicity against MCF-7 cell line with IC50 of 0.5-190nM. Compounds 8c and 9g showed preferential activity against Hela cells (IC50: 1.69 and 1.52 μM respectively). However, compound 5d showed notable potency against MCF-7 and Hela cell lines of 0.1 nM and 1.26 μM respectively. Kinase profiling for 4e showed the highest inhibition against a 20 kinase panel. Additionally, ADME prediction studies exhibited that compounds 4j, 5d, 5f, and 9f have drug-likeness criteria to be considered promising antitumor agents deserving of further investigation. SAR study showed that substitutions with 2-benzylidene hydra zino have a better fitting into PTK with enhanced antiproliferative potency. Noteworthy, the incorporation of hydrazino or ethanolamine moieties at position 2 along with small alkyl or phenyl at N-10, respectively revealed an extraordinary potency against MCF-7 cells with IC50 values in the nanomolar range.